2004
DOI: 10.1080/10473289.2004.10470967
|View full text |Cite
|
Sign up to set email alerts
|

The Regional Nature of PM2.5 Episodes in the Upper Ohio River Valley

Abstract: From October 1999 through September 2000, particulate matter (PM) with aerodynamic diameter Ն2.5 m (PM 2.5 ) mass and composition were measured at the National Energy Technology Laboratory Pittsburgh site, with a particle concentrator Brigham Young University-organic sampling system and a tapered element oscillating microbalance (TEOM) monitor. PM 2.5 measurements had also been obtained with TEOM monitors located in the Pittsburgh, PA, area, and at sites in Ohio, including Steubenville, Columbus, and Athens. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…Ohio River Valley and possible urban regions beyond were found to be the significant sources of PM and its precursors in the Pittsburgh area and at other regional sites included in the study. 17 The Steubenville Comprehensive Air Monitoring Program Study noted that PM concentrations Ͼ35 g/m 3 were observed at a site in Steubenville, PA. 18 Based on the results from previous studies, continuous PM 2.5 mass concentration and speciation data were collected at the three monitoring sites located in Central and Southeast Ohio, and the data were used in a source apportionment assessment of regional and local sources using PSCF analysis and PCA in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Ohio River Valley and possible urban regions beyond were found to be the significant sources of PM and its precursors in the Pittsburgh area and at other regional sites included in the study. 17 The Steubenville Comprehensive Air Monitoring Program Study noted that PM concentrations Ͼ35 g/m 3 were observed at a site in Steubenville, PA. 18 Based on the results from previous studies, continuous PM 2.5 mass concentration and speciation data were collected at the three monitoring sites located in Central and Southeast Ohio, and the data were used in a source apportionment assessment of regional and local sources using PSCF analysis and PCA in this study.…”
Section: Discussionmentioning
confidence: 99%
“…High concentrations from this source were always associated with time periods that have been shown to involve significant pollutant transport from the Ohio River Valley to the west and southwest. 17,19 The identified PM 2.5 sources are given in Figure 3. Figures 4-9 give the results of these various plots and the sources so identified for the PM 2.5 components at the CMU (Figures 4 -6) and NETL (Figures 7-9) sites, respectively.…”
Section: Unmix Output Interpretation and Sourcementioning
confidence: 99%
“…It is believed that secondary ammonium sulfate in the Pittsburgh area is dominated by transported material from the Ohio River Valley. 6,17,19 Therefore, the expectation is that local chemistry will be decoupled from chemical processes associated with the long-distance transport of pollutants. As shown in Figure 14, the secondary carbonaceous pollutants at each site showed the expected results in terms of their time series plots.…”
Section: Consistency In Reported Unmix Datamentioning
confidence: 99%
“…In addition, this source is also consistently associated with transport to the Pittsburgh area from the west or southwest, 10,22 a region high in SO 2 emission sources. 22 Facilities in this direction include coal-fired power plants, coke processing industries, steel mills, and other industrial sources located along the Ohio River from Steubenville, 50 km west of Pittsburgh, and other sources to the south and west of Steubenville. 22 The presence of NVOM and trace elements in lower concentrations in the source profile is consistent with lower concentrations of primary emissions from these sources, mixed with the high concentrations of secondary ammonium sulfate formed during transport to the Pittsburgh area.…”
Section: Nature Of the Resolved Sourcesmentioning
confidence: 99%
“…22 Facilities in this direction include coal-fired power plants, coke processing industries, steel mills, and other industrial sources located along the Ohio River from Steubenville, 50 km west of Pittsburgh, and other sources to the south and west of Steubenville. 22 The presence of NVOM and trace elements in lower concentrations in the source profile is consistent with lower concentrations of primary emissions from these sources, mixed with the high concentrations of secondary ammonium sulfate formed during transport to the Pittsburgh area. As indicated in Figure 5, this transported secondary material source is the major contributor to both PM 2.5 and ammonium sulfate at the CMU site during the time of the study.…”
Section: Nature Of the Resolved Sourcesmentioning
confidence: 99%